2023
DOI: 10.1097/pcc.0000000000003285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Resources and Inequities Among Pediatric Critical Care Facilities in Pakistan

Abstract: OBJECTIVES: To evaluate nationwide pediatric critical care facilities and resources in Pakistan. DESIGN: Cross-sectional observational study. SETTING: Accredited pediatric training facilities in Pakistan. PATIENTS: None. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: A survey was conducted using the Partners in Health 4S (space, staff, stuff, systems) framework, via email or telephone correspondence. We used a scoring system in which each item in our checklist was given a score of 1, if availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Abbas Q et al reported that of all the PICUs surveyed in the country, only 30% were staffed by paediatricians with training in PCCM. 12 Despite these documented barriers, the specialty has seen significant growth in recent years13m which is reflected by the linear growth of research output from the country noted in the current study. Several reasons come to mind for this increased output.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Abbas Q et al reported that of all the PICUs surveyed in the country, only 30% were staffed by paediatricians with training in PCCM. 12 Despite these documented barriers, the specialty has seen significant growth in recent years13m which is reflected by the linear growth of research output from the country noted in the current study. Several reasons come to mind for this increased output.…”
Section: Discussionmentioning
confidence: 66%
“…16 For every 500,000 Pakistani children age <14, there exists only 1 PICU bed compared to 1 bed/10,000 children in the United States and 1/1000 children in the United Kingdom. 12 This translates to a severe shortage of trained PCCM personnel. Those that exist experience an overwhelming volume of clinical work, especially in public-sector hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the general nurse-to-patient ratio in Pakistan is 1:50, in ICUs this ratio is 1:1.3-to-1:1.7, well below the expectation in developed countries (ratio 1: 1-to-2). 6 Task sharing and shifting is a concept being used by many healthcare systems and is also promoted by the WHO 7 to help address the shortage of healthcare workers in LMICs. Technology and clinical decision support systems (CDDS) can be used to augment the awareness of an evolving clinical state and timely communication intervention by less skilled healthcare workers in LMICs.…”
Section: Introductionmentioning
confidence: 99%